Hybrid Braking System: Electromagnetic + Disc Braking - Krushna Memane; Sakshi Mhaske; Gayatri Mind; Yash Kadam; A. A. Joshi (International Journal of Mechanical Dynamics and Systems Analysis, 2026)
The Hybrid Braking System combines electromagnetic braking and traditional disc braking to enhance vehicle safety, improve braking response, and reduce mechanical wear. This system integrates sensor fusion technologies, including ultrasonic and infrared sensors, to enable adaptive braking based on real-time road conditions. A PID-based control algorithm optimizes braking force distribution, ensuring a smooth and controlled deceleration. Additionally, the incorporation of regenerative braking allows for energy recovery, increasing vehicle efficiency and sustainability. The proposed system is designed to be cost-effective and scalable, making it suitable for a wide range of vehicles, from two-wheelers to four-wheelers. This project outlines the design, working principle, hardware implementation, and performance analysis of the hybrid braking system, demonstrating its potential to revolutionize modern braking technology.To offer better stopping performance, increased safety, and increased energy efficiency, the suggested Hybrid Braking System combines electromagnetic braking with traditional disc brakes. Conventional disc brakes are prone to wear, heat generation, and maintenance issues, but they offer dependable friction-based stopping capability. The technology greatly lowers mechanical wear and enhances response time by utilizing electromagnetic brakes, which functions without physical touch. In order to ensure smooth and steady vehicle control, the hybrid technique enables both braking mechanisms to work in tandem, with disc braking providing the final stopping force and electromagnetic braking handling beginning deceleration.The system continuously monitors obstructions, vehicle speed, and road conditions by merging ultrasonic and infrared sensors using sensor fusion technology, which increases adaptability. A PID-based control algorithm processes these inputs and intelligently divides the braking power between the two systems to maximize performance and avoid wheel lock or sliding.
Keywords: Adaptive Braking; Disc Braking; Electromagnetic Braking; Hybrid Braking; PID control; regenerative braking; sensor fusion